Adoption of Technology and the Unorganized Retailers - Rao, O. R. S, Joydeep Mookerjee, Subir Chattopadhyay (Mathematical Statistician and Engineering Applications, 2022)
In this paper, we give several possible interpretations and perspectives on retail technology adoption, all of which are grounded in carefully examining the relevant literature. Analyzing the many forms of retail technology, Global and Indian retailers of structured and Unorganized fashion have quickly incorporated new technologies. The impact of the covid-19 pandemic on India’s retail sector saw a dramatic transition due to the introduction of new technologies. The literature review covers various theories and understanding of how technology adoption models depend on available resources, as well as the challenges and objectives of the study, including the gap analysis and the target market of retailers. The customer sentiment will inform the retailers and the development companies of a new research framework. The applied aspects of technology adoption solutions must be understandable to stakeholders such as retailers and customers. These reviews are expected to get insight into the literature about the technology adoption status that underpins the evolution of technology adoption and how they could inform future endeavors in this area.